2018
DOI: 10.1177/1941874418801429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Language on Emergency Medical Service Use and Prenotification for Acute Ischemic Stroke

Abstract: Background and Purpose: Use of emergency medical services (EMS) is associated with decreased door-to-needle time in acute ischemic stroke (AIS). Whether patient language affects EMS utilization and prenotification in AIS has been understudied. We sought to characterize EMS use and prenotification by patient language among intravenous tissue plasminogen activator (IV-tPA) tissue plasminogen (IV-tPA) treated patients at a single center with a large Spanish-speaking patient population. Methods: We performed a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, previous studies have showed conflicting results on the impact of language barriers. Emergency medical service usage was actually reported higher in the Spanish-speaking patients than the English-speaking patients treated with IVT [18]. A retrospective single-center study showed that language discordance was not associated with acute stroke misdiagnosis among patients treated with IVT [19].…”
Section: Discussionmentioning
confidence: 97%
“…However, previous studies have showed conflicting results on the impact of language barriers. Emergency medical service usage was actually reported higher in the Spanish-speaking patients than the English-speaking patients treated with IVT [18]. A retrospective single-center study showed that language discordance was not associated with acute stroke misdiagnosis among patients treated with IVT [19].…”
Section: Discussionmentioning
confidence: 97%
“…The use of emergency medical services varies among different language-speaking patients [32]. EMS providers should be prepared when responding to emergency calls involving patients with limited language proficiency [33].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found no association between English or non-English preference and either mode of arrival or time to hospital presentation (17,32). Three studies were carried out at the same New York City institution using data from patients who received IV-tPA (18)(19)(20). One found that Spanish speakers were more likely than English speakers to have arrived by EMS after adjusting for confounders, while prenotification rates were not significantly different among those who utilized EMS.…”
Section: Pre-stroke Care: Awareness and Preventive Treatmentmentioning
confidence: 99%
“…One found that Spanish speakers were more likely than English speakers to have arrived by EMS after adjusting for confounders, while prenotification rates were not significantly different among those who utilized EMS. Median symptom onset-to-door and DTN times did not differ between Spanish and English speakers (18). A second study investigated the role of language-concordant vs. discordant encounters, defined by whether the primary treating physician and the patient possessed fluency in the same language.…”
Section: Pre-stroke Care: Awareness and Preventive Treatmentmentioning
confidence: 99%